The prevalence of performance-related musculoskeletal disorders in fine arts faculty students and academics - (:unkn) unknown (IOS PRESS, 2020)
BACKGROUND: While professional musicians may have a high incidence of musculoskeletal pain, there are few studies on the performance-related musculoskeletal disorders (PRMD) in visual artists. OBJECTIVE: To assess the prevalence and probable risk factors of PRMD in visual artists. METHODS: The study population comprised the students and academics of fine arts faculty. The Rapid Entire Body Assessment (REBA) and the Cornell Musculoskeletal Discomfort Questionnaires were used to evaluate posture and pain, respectively. RESULTS: The study included 197 participants (140 women, 57 men). The mean REBA score was 5.2. The sculptors who worked in marble sculpting had the highest REBA scores. Of the participants, 88.8% reported musculoskeletal pain. The pain severity of 64.0% of the participants was 3 (very uncomfortable with a reduction in activity) and/or 4 (pain interferes with the ability to work). The PRMD prevalence was 64.0%, and significantly higher in women than in men (p < 0.05). CONCLUSIONS: Musculoskeletal pain in visual artists is extremely prevalent. Mean REBA score of 5.2 corresponds to a medium risk assessment accompanied by guidance to further investigate, change soon. The policy makers in fine arts faculties who are responsible for student and employee health should prioritize strategies to prevent and manage musculoskeletal pain.
Keywords: Ergonomics; visual arts; musculoskeletal pain; occupational medicine; epidemiology; MUSICIANS; PAIN; QUESTIONNAIRE; ARTISTS